Mast cell metabolism in cancer: an underexplored frontier demanding more attention - Frossi, Barbara; Scialpi, Giuseppina Beatrice; Tonon, Silvia; Jachetti, Elena (Frontiers in Immunology, 2025)
Cancer metabolism is gaining considerable attention. Tumor cells are characterized by a peculiar metabolic state to sustain the continuous demand of energy and metabolites needed for their proliferation and long-term survival. Such metabolic alterations extend beyond cancer cells, affecting multiple components of the tumor microenvironment (TME), including immune cells, stromal cells, and endothelial structures, and are influenced by both local and systemic conditions. Mast cells (MCs) are innate immune cells capable of both pro- and anti- tumorigenic functions and with the potential to modulate the activity of bystander immune cells. Nevertheless, despite their established importance in the TME, the impact of MCs in modulating cancer metabolism remains largely unexplored. This review outlines current findings regarding the metabolic conditions in the TME that modulate MC function, and, vice versa, how MC-derived metabolites can influence tumor progression, acting both on cancer and stromal cells. We focus on four main altered conditions in the TME: glucose metabolism, amino acid availability, lipid composition, and hypoxia. As studies investigating MC metabolism in cancer are limited, we also discuss relevant literature addressing how metabolic stimuli influence MC activity, as well as the effects of MC-derived metabolites on target cells, in non-cancer physiological or pathological conditions, to highlight possible mechanisms that deserve further investigation in cancer settings. Deeper investigation of MC-related metabolic networks in the TME is needed, not only to elucidate their functional modulation in response to current metabolic interventions, but also to explore their potential as therapeutic targets in the context of cancer metabolism.